Ludovico Domenichi’s La donna di corte (1564) and the Paradoxical Representation of Female Perfection - Valencia, María Dolores (Renaissance and Reformation / Renaissance et Réforme, 2023)
Having dealt with the womanly virtues and what they share with male virtues in his work La nobiltà delle donne (1549), Ludovico Domenichi focuses in La donna di corte (1564) on the amorous behaviour of a specific type of woman: the palace lady, the harmonious counterpart to the courtier. In this article, I analyze the underlying ambiguity of Domenichi’s message. Making an effort to defend the perfection of women without being highly critical of men, Domenichi suggests that the emancipation implied by the public role of court entertainment is in fact constantly controlled through an education based on pudicitia and honestà. He has no intention of changing either the social order or the role of women.